Survey of innate immune responses to Burkholderia pseudomallei in human blood identifies a central role for lipopolysaccharide. - Chantratita, N; Tandhavanant, S; Myers, N; Seal, S; Arayawichanont, A; Kliangsa-Ad, A; Hittle, L; Ernst, R; Emond, M; Wurfel, M; Day, N; Peacock, S; et al. (2013)
B. pseudomallei is a gram-negative bacterium that causes the tropical infection melioidosis. In northeast Thailand, mortality from melioidosis approaches 40%. As exemplified by the lipopolysaccharide-Toll-like receptor 4 interaction, innate immune responses to invading bacteria are precipitated by activation of host pathogen recognition receptors by pathogen associated molecular patterns. Human melioidosis is characterized by up-regulation of pathogen recognition receptors and pro-inflammatory cytokine release. In contrast to many gram-negative pathogens, however, the lipopolysaccharide of B. pseudomallei is considered only weakly inflammatory. We conducted a study in 300 healthy Thai subjects to investigate the ex vivo human blood response to various bacterial pathogen associated molecular patterns, including lipopolysaccharide from several bacteria, and to two heat-killed B. pseudomallei isolates. We measured cytokine levels after stimulation of fresh whole blood with a panel of stimuli. We found that age, sex, and white blood cell count modulate the innate immune response to B. pseudomallei. We further observed that, in comparison to other stimuli, the innate immune response to B. pseudomallei is most highly correlated with the response to lipopolysaccharide. The magnitude of cytokine responses induced by B. pseudomallei lipopolysaccharide was significantly greater than those induced by lipopolysaccharide from Escherichia coli and comparable to many responses induced by lipopolysaccharide from Salmonella minnesota despite lower amounts of lipid A in the B. pseudomallei lipopolysaccharide preparation. In human monocytes stimulated with B. pseudomallei, addition of polymyxin B or a TLR4/MD-2 neutralizing antibody inhibited the majority of TNF-α production. Challenging existing views, our data indicate that the innate immune response to B. pseudomallei in human blood is largely driven by lipopolysaccharide, and that the response to B. pseudomallei lipopolysaccharide in blood is greater than the response to other lipopolysaccharide expressing isolates. Our findings suggest that B. pseudomallei lipopolysaccharide may play a central role in stimulating the host response in melioidosis.